PROFITABILITY ANALYSIS AND DETERMINANTS OF TOMATO OUTPUT IN FEDERAL CAPITAL TERRITORY (FCT), ABUJA, NIGERIA - Agbonika, D.A.; Alawiye, M.A.; Oloidi, J.O.; Muhammed, M.; Oloye, F.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined the profitability and determinants of tomato output in the Federal Capital Territory (FCT), Abuja, Nigeria. Primary data were collected from 80 tomato farmers across six Area Councils using purposive and proportionate random sampling techniques. Descriptive statistics, gross margin analysis, and Ordinary Least Squares (OLS) regression were used in achieving research objectives. The result showed that sampled farmers were predominantly male (65.0%), young (80.0%) with mean age of 33.7 years, and largely low experienced (73.8%) with six or fewer years in tomato farming. Gross margin analysis revealed a mean loss of −₦971,057 per season, a benefit-cost ratio of 0.786, and only 11.3% of farms achieving positive returns which stands as a sharp deterioration from the pre-fuel subsidy profitable baseline. Fuel price change was the most strongly perceived increase (Likert mean = 3.49; t = 3.956, p < 0.001). OLS estimation identified seed price change (β = −0.473, p = 0.028) and the composite constraint score (β = 1.425, p = 0.002) as the only statistically significant determinants of log yield. The study thus concluded that tomato farming unprofitability in the FCT was influenced by the prevailing input price conditions of fertilizer, fuel, labour, and agrochemical costs, and the seed price changes was the major determinant of declining tomato yield. The findings thus recommend targeted price stabilisation mechanisms, improved subsidy delivery, and credit access expansion to restore the viability of peri-urban tomato production.